Efektivitas Bahan Ajar Berbasis Penemuan Terbimbing Untuk Meningkatkan Kemampuan Komunikasi Matematis Peserta Didik Kelas VIII SMP - Wiga Ariani (Journal on Education, 2020)
The aim of this research was to determine the effectiveness of guided inquiry based instructional materials in improving students’ mathematical communication ability. The subject of the research was 34 the students in class VIII7 of SMPN 12 Padang. The effectiveness was viewed from the students’ mathematics communication ability after learning by using guided inquiry based instructional materials. The communication skills of students are obtained from tests given in the form of essay tests with 6 items in the Pythagoras theorem lesson. I scoring rubrics indicators of mathematical communication ability were developed by referring to NCTM (1989) and Sumarmo (2003). The scoring results will be compared with the Minimum Completion Criteria (KKM) set by the school with a value of 75. There were 34 students taking essay tests. The value of students ≥ 75 as many as 24 people with a percentage of 70.5%, while the value of 10 other people < 75 with a percentage of 29.5%. More than 65% of students are above KKM. so that guided inquiry based instructional materials can improve students' mathematical communication ability